Methodological approach to the assessment of the existing level of preparedness of military units for special tasks performed at special events and activities for the disposal of armed criminals and other persons of high social danger - Gorodnov, V. P.; Ovcharenko, V. V.; Yemanov, V. V. (Honor and Law, 2019)
The methodical approach to the assessment of the existing level of preparedness of military units for special tasks performed at special events and activities for the disposal of armed criminals and others who represent an increased danger to the public in order to prepare proposals leader (commander) to make an informed decision.